Community-based curriculum for inter-ethnic education and violence prevention - Iouri Zagoumennov; Ihar Zahumionau (Universidad Autónoma de Madrid, 2015)
While Belarus has been uniquely marked in its region by a history of productive coexistence between the majority of the population and the country's diverse ethnic, religious and national minorities the country is now faced by new challenges from an influx of recent refugees from the republics of the Former Soviet Union. This combined with increasing stresses on the nation's economy and dislocations due to fundamental changes in social organisation may potentially compromise the tradition of tolerance and good will. Especially sensitive are the cases of those groups which are associated with recent and ongoing conflicts in the Russian Federation. This may particularly be problematic with Chechens, and other adherents of Islam. The Roma may also face difficulties. Further potential complications could emanate from pressures by Russian nationalist groups exerting external influences and extreme nationalist formations developing internally. It is important that action is taken now to implant the lessons of historic coexistence in the emerging generation of Belarusian citizens.